Pakistan-India after Pulwama Attacks: Theoretical Assessment - Muhammad Waqas Haider; Tahir Mahmood Azad, (ASIAN Journal of International Peace & Security (AJIPS), 2022)
This research paper analyses the impact of the Pulwama attacks on reshaping Pakistan and India relationship through the lenses of major theories of International Relations: Realism, Liberalism and Constructivism. Pakistan and India have deep rooted territorial disputes due to which their relations remained in a state of flux since partition. The relations between Pakistan and India remain at the centre stage of the international arena both being nuclear powers. However, the recent rise in tensions following the Pulwama attacks 2019 gave new dimensions to the relations. The paper gives a brief overview of the recent history of relations between the two countries leading to a short description of the Pulwama attacks. Furthermore, the situation has been assessed by laying out the theoretical dimensions of the essay and explains the key tenets of these theories: Realism, Liberalism and Constructivism. Then, the paper focuses on the impact of incidents on inter-state relations in the light of key assumptions of these theories. Additionally, the research predicts future relations based on discussion in light of theories and recommends a way forward for peaceful relations between the two nuclear neighbours.